Puerto Rico - Thompson, Kathleen (Milwaukee, WI : Raintree Publishers, 1986)
Discusses the history, economy, culture, and future of Puerto Rico. Also includes a chronology, pertinent statistics, and maps.
"A Turner book."
5.0
5-8
Keywords: Puerto Rico -- Juvenile literature; Puerto Rico; Puerto Rico